Comportamiento financiero de las microempresas comerciales de la ciudad de Buena Fe y su incidencia económica en su crecimiento, año 2012 - Almeida Perero, Cindy Katherine (2013)
The thesis project was performed at the Canton Trade Microentrepreneurs good faith with the aim of meeting the financial performance and its economic impact, in order to guide the entrepreneurs the importance of a effective and efficient management of its resources, implementing strategy short-term financial help maximize the value of your business. It is important to not eth at obtaining information was made by apply ing survey and interviews of the Canton Trade Microentrepreneurs BuenaFe, the survey consisted of15 questions, information thath contribute to the realization ofthis research The study of behavioral finance, which have demonstrated weaknesses in financial management, which affected their li quidity and profitability, thus highlighting the importance of meeting the working capital management which is manage cash, accounts receivable, inventory and accounts payable, andthe completionof the financial statementswiththe reasonsand financial indicatorsin which we tested positive for implementing this project. The main objective ofthis study is to increase theworking capitalto implement the policyand financial strategyof working capitalthat focuses onthe management ofcurrent assetsandcurrent liabilities.